The influence of Career Development and Management Support on Employee Performance PT Bank Rakyat Indonesia (Persero) Wonosari Branch Office mediated by Employee Engagement - Nugraha, Yogi; Siswanti, Yuni; Sabihaini, Sabihaini (West Science Journal Economic and Entrepreneurship, 2023)
This study aims to analyze the effect of career development and management support on employee performance of PT Bank Rakyat Indonesia (Persero) Wonosari Branch Office mediated by employee engagement. This study uses Partial Least Square to determine the relationship so that researchers use the Smart PLS application to determine the relationship between employee performance variables. The sample in this study were employees within the scope of PT Bank Rakyat Indonesia (Persero) Wonosari Branch Office totaling 90 employees. This study uses quantitative data by distributing questionnaires to all samples studied. Based on outer testing, this study passed the validity and reliability tests. While based on the Inner model, the results show that management support positively has a significant positive effect on employee engagement. However, career development on employee performance, management support on employee performance, career development on employee engagement, management support on employee engagement, has no significant effect. For PT Bank Rakyat Indonesia (Persero) Wonosari Branch Office, it is recommended to further improve company facilities in this case management support and career development in order to improve employee performance in the future. For further research, it is expected to increase the number of respondents, because the amount of research data greatly affects the results of the analysis.